Gerontagogia dialógica intergeracional para autoestima e inserção social de idosos - Serra, Deuzimar Costa (2012)
The thesis addresses a topic relevant to current social context, education for older adults, considering demographic growthand increased life expectancy in Brazil by the need of educational proposals concerning education for lifelong, mediated by the guarantee of the rights to education; It aims to analyze the gerontological activities, unveiling contributions to literacy mediated intergenerational dialogue to self-esteem and social integration of the elderly. The research has a qualitative approach as a reference, modality in action research as the main methodological procedure, and Culture circles used to work generating themes removed from the context of people surveyed and the Elderly Statute (Estatuto do Idoso). The process of literacy and lifelong formation, guided by Gerontagogical Dialogic Intergenerational,epistemological fundamentals from Paulo Freire, in the field of history and memory, among other studies converge and converse with the elements found in this investigation.Regarding the methodological approach, were used semi-structured interviews with scripts, questionnaires and participant observation; Individuals of this research are called eagles of love (the elderly), life (children), hope (grandchildren) and light (teachers).The socio-demographic data are results of the questionnaires with twenty (20) elderly (eagles love) in cutting age (60 to 85 years of age), who participate in the Intergenerational Project and revealed the social educational and economic true, result of a life story that conditioned by several reasons to remain outside the social inclusion process. How had no opportunity to study because there was no school in the locality of residence, all, without exception, changed the countryside for the urban areain search of better living conditions, especially to put their children in school, get form them as a reward and projection of dreams that could not achieve. The survey information after the interview and the activities of the culture circle, confirmed that work of this nature, mediated by Gerontological intergenerational dialogue contribute to self-esteem and social integration of older people, found in the dialogues and attitudes of the eagles, as the apex of the results. Reverberated in the construction of this thesis: the appropriation of reading and writing as a process that maximizes the relation between knowledge, reflection, action and requirement of the rights guaranteed in the Elderly Statute; digital literacy, participation, persistence and engagement in activities with joy and gestures of solidarity; personal enhancement; involvement of children and grandchildren with the improvement of family relations and change in conceptions of old age. However, this explicit need to be included in the Educational Politicsa pedagogy pledge not only insertion of old people in school and non-school contexts, as well as the inclusion in the proposed curriculum of basic education, with contents that include education and intergenerational process aging, this approach is essential that the proposals of teacher training courses, mainly pedagogy courses in, can provide the skills to work, especially in classes EJAI (Education for Youth, Adults and Elders), anchored on the contribution of Gerontological, from the new paradigms about senescence and the aging process, and thus contribute to lifelong education.